Recaudación tributaria municipal y su ejecución presupuestal en la Municipalidad Provincial de Maynas, 2019 - 2020 - Pérez Flores, Anllelo Gabriel (2022)
Collection by municipal taxes is perceived as the ideal mechanism to meet the needs of a locality through budget execution by municipal managers, for this it is considered important to analyze the characteristics of budget collection and execution, for this it was developed a study whose general objective is to identify the Municipal Tax Collection and Execution in the Provincial Municipality of Maynas, 2019-2020, proposing a descriptive and non-experimental design investigation, considering as a data collection instrument collection sheets that allowed collecting data. data from the study sample constituted by budgetary information of the analyzed entity, the investigation identified that municipal taxes represent 8.6% and 5.34% in relation to the allocation of the period, that the budget execution represents 11.13% and 7.47% in reference to the execution of the entire plieg or budgetary, that the property tax is the one that presents the most representativeness to the collection, followed by the Tax on slot machine games and that the generic of goods and services is the expense that most affects the financing of the item followed by the generic for expenses of personnel, concluding that the tax collection and the execution of the municipal tax item are not very significant, presenting a negative trend in the study period.